2002
DOI: 10.1021/jp014277c
|View full text |Cite
|
Sign up to set email alerts
|

Extremely Slow Counterion Dynamics in Xanthan Liquid Crystal through 23Na and 14N NMR

Abstract: To describe the structure and dynamics in a lyotropic xanthan liquid crystal, we have done 23 Na and 14 N NMR experiments. The spectra are consistent with a powder average over randomly oriented liquid-crystalline domains. From 14 N quadrupolar echo experiments it was concluded that the exchange among the several micron sized domains is slow with residence times in the millisecond range. Conventional spin-lock experiments ( 14 N and 23 Na) as well as spin-lock experiments filtered through the quadrupolar spin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 31 publications
0
14
0
Order By: Relevance
“…The above publications spurred an increase in the use of 14 N NMR as a probe of LCs, lipid bilayers and related systems, with a number of reports studying 14 N linewidths and relaxation [180][181][182][183][184][185][186][187][188][189][190][191], and others investigating quadrupolar splittings [192][193][194][195][196][197][198][199][200][201][202][203][204][205][206][207][208][209][210].…”
Section: Aligned Systemsmentioning
confidence: 99%
“…The above publications spurred an increase in the use of 14 N NMR as a probe of LCs, lipid bilayers and related systems, with a number of reports studying 14 N linewidths and relaxation [180][181][182][183][184][185][186][187][188][189][190][191], and others investigating quadrupolar splittings [192][193][194][195][196][197][198][199][200][201][202][203][204][205][206][207][208][209][210].…”
Section: Aligned Systemsmentioning
confidence: 99%
“…This often is the case in soft-condensed matter, where the correlation times can be rather long, but with relatively small values of the corresponding coupling constants. Equation [6] now becomes d*/dt ϭ Ϫi͓H* S , *͔ ϩ f ͑*͒ [7] with the relaxation superoperator…”
Section: Time Evolution Of the Density Operatormentioning
confidence: 99%
“…This inhomogeneous broadening makes an accurate measurement of the spectral density at zero frequency J 0 in ordered material difficult, if not impossible. Recently, it has been shown that in the case of a powder-type variation of the static quadrupolar coupling, slow dynamics is probed more efficiently by applying a lock through a radio-frequency field (6). Another method to effectively eliminate the inhomogeneous broadening is based on delayed acquisition (37)(38)(39).…”
Section: Delayed Acquisitionmentioning
confidence: 99%
See 2 more Smart Citations